(untitled) (LACCEI, 2024)
The objective of this article is to carry out research through the review of updated scientific publications on the working conditions of conductive materials, focusing mainly on the studies of three continents recognized in technological and scientific topics, especially on the different types of new conductive materials with significant contributions. Countries from Latin America, North America and Europe were selected to identify the main conductive materials, their characteristics, and properties, to analyze possible solutions to everyday situations. Therefore, a process of search and interpretation of 51 articles of references from countries belonging to this group was carried out, to achieve the elaboration of an information matrix that served in the organization and establishment of the useful contents for the article. Subsequently, the results of the research, ideas and debates were presented in a clear, concise, and reliable manner, using the analysis of the leading materials and their characteristics outside the country, to have a perspective and recognition of attention to the impact generated during the development of projects with respect to economic issues and their use.